The Influence of Eco-Friendly Products, Product Quality, and Price on Purchase Decisions from an Islamic Business Perspective - Chusnul Khotimah; Hanif; Is Susanto (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the influence of Eco-Friendly Products, Product Quality and Price on Purchase Decisions of Garnier products in the Perspective of Islamic Business in Generation Z society in Bandar Lampung. This study was conducted by conducting a pre-survey of 33 respondents with the results still divided preferences for Garnier compared to other brands (48.5%) and not all respondents know some Garnier products that are environmentally friendly and do not feel comfortable with Garnier products (45.5%). in addition (63.6%) consider the price before buying and only (33.3%) buy granier products regularly. The study uses a quantitative approach with the nature of associative causal research. The research population is the Gen Z community in Bandar Lampung. Involving 100 sample respondents determined through the Slovin formula using criteria. Data collection using a questionnaire. Data is processed using SmartPLS 4. The results of the study found that environmentally friendly products, quality, and price had a positive and significant effect on Garnier's purchasing decisions, both partially and simultaneously, with price as the most dominant factor